(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In terms of export, NR is not a traditional item of Indian export. Despite this, the government has prioritised NR exports since 2001, when quantitative restrictions (QRs) on imports were lifted. The promotion of NR export is being promoted as a counter-strategies to the wild volatility in domestic NR price movements caused by the massive influx of NR imports into the country. The rubber-consuming industry in India has been importing NR in large quantities in recent years, taking advantage of the country’s import duty structure. Even though the current demand-supply imbalance and deficit do not call for a robust export promotion strategy for natural resources, the Board will concentrate on export promotion in order to increase the sector’s export competitiveness and capabilities so that exports can be made whenever the price environment is favourable. The Board is taking a number of actions to encourage exports and assist Indian exporters in surviving on the international market. The Board’s responsibilities include promoting the NR brand, participating in trade shows, and offering training on natural rubber export management, export procedures, and import policy. Therefore, it has become necessary to assess the rubber board’s effectiveness from the viewpoint of the rubber farmers in promoting natural rubber exports from India. This article makes an effort to assess the impact of rubber boards on India’s exports of natural rubber.